Performance analysis of cryptography algorithms for implementation of secured cloud based online voting system - Karanam Subramanyam Gururaj; Kampalappa Thippeswamy (Institute of Advanced Engineering and Science, 2023)
Any democratic country intends to conduct the elections in a smooth and fair manner such all the citizens of the country participate and elect their leader who can involve himself/herself for the development of the country. Inspite of wide publicity and measures taken for ensuring the participation of all the citizens in the election process, most of the countries are unable achieve 100% voting rate in elections. Among the many reasons for reduction in voting rate, migration of the voters is one of the major reasons for reduction in voting rate. Even though technology and online services have been used in almost all the aspects of day-to-day activities, online features have not been utilized in the process of voting during elections. This paper tries to analyze the performance of the cloud based secured framework by implementing it using PHP and mySQL. Security of the framework is implemented using rivest shamir adleman (RSA), advanced encryption standard (AES) and Blowfish cryptography algorithms.